The Retention of the Mandatory Death Penalty in Trinidad and Tobago: An Ongoing Human Rights Concern - Yearwood, Rico J.; Newton, Stefan K. (Serikat Pengajar Hak Asasi Manusia Indonesia, 2022)
The Commonwealth Caribbean forms a significant part of the Global South, accounting for approximately 15% of its population. Among these nations, the Republic of Trinidad and Tobago remains the only state to retain the mandatory death penalty, in open defiance of its international human rights obligations. This legal persistence represents a critical human rights concern, particularly within the context of the Global South, where legacies of colonial jurisprudence continue to influence domestic legal systems. While prior research has addressed the broader decline of the death penalty and the role of final appellate courts in human rights protection, few studies have critically examined how judicial authority in postcolonial states sustains punitive legacies. This article contributes to Global South human rights scholarship by investigating how competing regional and imperial legal institutions—namely, the Judicial Committee of the Privy Council (JCPC) and the Caribbean Court of Justice (CCJ)—shape the retention of the mandatory death penalty in Trinidad and Tobago. Employing a comparative doctrinal analysis of case law from both courts, the study evaluates their respective approaches to the death penalty and the protection of fundamental rights. It reveals that while the CCJ prioritises human rights principles, the JCPC’s jurisprudence continues to legitimise the constitutionality of the mandatory death penalty, thereby enabling Trinidad and Tobago to avoid compliance with evolving international human rights standards. The findings demonstrate that the JCPC’s stance undermines regional human rights development and weakens the potential for progressive legal reform in the Global South. The article concludes that the continued reliance on outdated legal interpretations from an external appellate body is untenable for a democratic state committed to human dignity. It calls on Trinidad and Tobago’s Parliament to take decisive legislative action to abolish the mandatory death penalty and align national law with contemporary human rights norms.